ANALISIS NILAI KEKASARAN PERMUKAAN PROSES CNC MILLING BAJA AISI 1045 METODE RESPON SURFACE - Egi Endrian; Muhammad Subhan; Yuliyanto Yuliyanto (Politeknik Manufaktur Negeri Bangka Belitung, 2021)
Minimum surface roughness is the desired goal in the MORI SEIKI MV-40M CNC machining process with the right machining process parameters in order to obtain a minimum workpiece surface roughness response. The results of the study indicate that to reduce the variation of the response simultaneously. To obtain minimum workpiece surface roughness on AISI 1045 steel with a variation of 0.18 mm infeed depth parameter (factor A level 1), feed rate 60 mm/min (factor B level 1 and spindle rotation 800 RPM (factor C level 2) with a The resulting roughness is 1,169 m.